Acetylcholine-induced coronary spasm in patients with unobstructed coronary arteries is associated with elevated concentrations of soluble CD40 ligand and high-sensitivity C-reactive protein. Issue 2 (March 2015) - Ong, Peter; Carro, Amelia; Athanasiadis, Anastasios; Borgulya, Gabor; Schäufele, Tim; Ratge, Dieter; Gaze, David; Sechtem, Udo; Kaski, Juan Carlos
Abstract : Objectives: To assess whether epicardial and microvascular coronary artery spasm in response to acetylcholine (ACH) is associated with markers of inflammation, platelet stimulation, and endothelial activation in patients with angina and unobstructed coronary arteries. Background: Patients with angina pectoris despite angiographically normal coronary arteries represent a diagnostic and therapeutic challenge. Both impaired coronary microvascular dilatory responses as well as diffuse distal epicardial and microvascular coronary artery spasm have been described as possible pathogenic mechanisms. Although inflammation has been proposed to play a pathogenic role in angina, an association between ACH-induced coronary vasospasm and inflammation in Caucasians has not been reported previously in this context. Patients and methods: We assessed 62 consecutive patients (26 men, age 60±10 years) with chest pain despite angiographically unobstructed coronary arteries (<50% stenosis) who underwent intracoronary ACH testing for the diagnosis of coronary artery spasm. High-sensitivity C-reactive protein (hs-CRP), e-selectin, neopterin, and sCD40L concentrations were measured in all patients before ACH testing. The ACH test was considered to be 'positive' in the presence of (a) angina and at least 75% coronary diameter reduction (epicardial coronary artery spasm) or (b) ischemic ST-shifts and angina in the absence of epicardial spasm (microvascular spasm). Eight patients without angina pectoris served as a control group. Results: The ACH test was positive in 48 patients (77%). Twenty-seven patients had epicardial spasm (56%) and 21 patients had microvascular spasm (44%). Epicardial spasm was diffuse in 26 patients (96%) and focal in one patient (4%). Elevated hs-CRP, e-selectin, and sCD40 ligand concentrations were significantly ( P ⩽0.05) associated with a positive ACH-test response. Hs-CRP (odds ratio 1.54, confidence interval 1.02–2.33, P =0.04) and sCD40 ligand (odds ratio 1.001, confidence interval 1.00–1.001, P =0.003) were predictors for a positive ACH test on multivariate analysis. None of the patients in the control group developed epicardial or microvascular spasm during ACH testing. Conclusion: Epicardial and microvascular coronary spasm in response to ACH correlate significantly with hs-CRP and sCD40 ligand concentrations in patients with angina pectoris and angiographically unobstructed coronary arteries. These results suggest that an association exists between inflammation and coronary artery spasm in patients with angina pectoris despite unobstructed coronary arteries and studies are needed to explore the mechanisms underlying this association.